REVITALIZATION OF ISLAMIC-BASED GOVERNANCE PRINCIPLES IN EARLY CHILDHOOD EDUCATION INSTITUTIONS: A CASE STUDY OF PAUD INSTITUTIONS IN WEST JAVA - Didi Suradi; Ahmad Syukron; Harapandi Dahri (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
This study examines the revitalization of Islamic-based governance principles in Early Childhood Education (PAUD) institutions in West Java through a qualitative case study approach. The research aims to analyze the implementation of governance principles grounded in Islamic values, particularly amanah (trustworthiness), musyawarah (consultation), and ‘adl (justice), within institutional management practices. Data were collected through in-depth interviews, observations, and document analysis involving school administrators, teachers, parents, and institutional stakeholders. The findings reveal that the implementation of governance principles in Islamic PAUD institutions is moderately effective but varies across governance dimensions. Financial transparency recorded the lowest implementation level at 42%, while communication with parents achieved the highest score at 83%. Transparency in learning programs reached 75%, whereas institutional policy transparency and organizational structure scored 67% and 58%, respectively. Stakeholder participation showed strong involvement from foundations (92%), parents (78%), and teachers (72%), but relatively weak participation from communities (25%) and local governments (33%). In terms of resource management efficiency, time management obtained the highest score (74%), followed by facilities management (71%), program effectiveness (68%), financial efficiency (63%), and human resource management (58%). The study also found that accountability mechanisms in teacher performance evaluation and program monitoring were relatively strong. The integration of Islamic ethical values into governance practices strengthens institutional sustainability, stakeholder trust, and educational quality. These findings contribute both theoretically and practically to the development of Islamic education management and provide recommendations for strengthening governance systems in PAUD institutions in Indonesia.